Directions of correctional and speech therapy work in the development of speech in early childhood - Makhmudova Madinaxon Sobirxonovna; Siddikova Bakhtigul Kabirjon kizi (Genius Journals, 2025)
The article contains ideas about the features of the development of speech in early childhood, the directions of correctional and speech therapy in the development of speech in early childhood, and the functions of speech in early childhood
Keywords: Early childhood; stages of speech development; speech experience